Comparative cost-effectiveness of tildrakizumab and other commonly used treatments for moderate-to-severe psoriasis. (3rd October 2021) - Wu, Jashin J.; Jia, Xiaoying; Zhao, Yang; Carrico, Justin; Brodtkorb, Thor-Henrik; Mendelsohn, Alan; Lowry, Simon; Feldman, Steven R.; Armstrong, April
Abstract: Objectives: To compare the cost-effectiveness of tildrakizumab with other commonly used biologics and apremilast as the first-line treatment for moderate-to-severe plaque psoriasis from a US health plan's perspective. Methods: A 10-year cost-effectiveness model was developed to compare the incremental cost per extra month with a Psoriasis Area and Severity Index (PASI) 75 response. Patients were assumed to receive one of the treatments evaluated as their first-line treatment at the outset of the analysis. Nonresponders (PASI <75) discontinued their current treatment; 25% went on to receive a mix of topical therapies, phototherapies, and other systemic therapies, while 75% received a second-line therapy before receiving a mix of topical therapies, phototherapies, and other systemic therapies. Direct medical costs were calculated based on drug acquisition, administration, and monitoring costs. Results: The incremental cost per extra month a patient had a PASI 75 response was lowest for brodalumab ($3, 685), infliximab ($4, 102), apremilast ($4, 770), and tildrakizumab ($5, 150), followed by risankizumab ($5, 319), secukinumab ($5, 675), guselkumab ($5, 784), ixekizumab ($5, 900), adalimumab ($5, 943), ustekinumab ($6, 131), etanercept ($6, 618), and certolizumab pegol ($13, 476). Conclusion: Tildrakizumab was among the most cost-effective first-line treatments for moderate-to-severe psoriasis and was more cost-effective than risankizumab, secukinumab, guselkumab, ixekizumab, adalimumab, ustekinumab, etanercept, and certolizumab pegol.